Degraded Teak Forests of Rajasthan and their Rehabilitation - Singh, Bharat (Indian Forester, 1962)
Degraded type of teak grows in the southern parts of Rajasthan, which needed proper tending and rehabilitation operations. This work was taken up during the Second Five-Year Plan period and the achievements have been encouraging. The details of these rehabilitation operations and the results obtained so far have been discussed.